Barriers to effective management of primary postpartum haemorrhage following in-hospital births in northwest Ethiopia: healthcare providers' views using a qualitative approach - Tiruneh Bewket; Fooladi Ensieh; Plummer Virginia; McLelland Gayle (BMC, 2022)
Abstract Background Data showed that postpartum haemorrhage contributed to over 40% of in-hospital deaths of Ethiopian women. However, little is known about the barriers to effective management of primary postpartum haemorrhage. This study aims to explore the views and experiences of maternity healthcare professionals about the barriers to managing primary postpartum haemorrhage following in-hospital births in northwest Ethiopia using the 'Three Delays' model as a conceptual framework. Methods A qualitative descriptive study was employed at two tertiary referral hospitals between December 2018 and May 2019. Forty-one maternal healthcare providers, including midwives, midwifery unit managers, and obstetricians, participated in this study. Individual face-to-face interviews, focus group discussions, and self-administered open-ended questionnaires were used to collect data. A framework analysis approach was used for the qualitative data analysis. Themes were identified based on the Three Delays model of 'delay the decision to seek care', 'delay arrival at a health facility', and 'delay the provision of appropriate and quality care'. Results Participants reported several modifiable issues when managing primary postpartum haemorrhage, and all were linked to a delay in receiving appropriate and quality care due to limited resources. Five sub-themes were identified: 'workforce', 'communication issues between healthcare providers', 'systemic issues', 'education, training, and resourcing issues', and 'lack of identification and referral'. Conclusion Maternal healthcare providers in these hospitals require training in managing a birthing emergency. In addition, the birth units need adequate supplies and continuous essential services.